Pedagogising Virtual Reality Technology - Verner Larsen (Nordic Journal of Comparative and International Education, 2023)
Digital technology has increasingly influenced all areas of education, including higher education, with subject-specific technologies developed for professional contexts alongside general communication and collaboration tools. This article draws on a case study conducted in a bachelor programme within building construction design in Denmark, tracking how teachers converted technical knowledge about virtual reality into teaching practice. This transformation process has crystallised different pedagogies, even within the same course. One pedagogical aim was for students to learn to use virtual reality (VR) as a professional competence, while another was to use VR as a tool for learning subject content (building design). This case study raises general issues regarding teachers' use of technology for teaching, addressed in the research tradition of technological, pedagogical and content knowledge (TPACK). However, to delve deeper into the educational transformation processes, this article adds an educational sociological perspective, including concepts from Legitimation Code Theory (LCT). With this background, this article raises new questions about the TPACK concept and discusses how the technological knowledge domains in the TPACK model can be differentiated to reflect various digital technologies and their functions, particularly in professional education.